ИНГЛИЗ ТИЛИ ДАРСЛАРИДА ПЕДАГОГИК ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШ - Абдусаттаров М. (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The article discusses the role and place of pedagogical technologies in improving the effectiveness of teaching students in English classes in secondary special schools.